2017
DOI: 10.1007/s40265-017-0785-2
|View full text |Cite
|
Sign up to set email alerts
|

Early Use of Ceftaroline Fosamil in the United States Veterans Health Care System

Abstract: Background Ceftaroline fosamil is U.S. FDA-approved for acute bacterial skin and skin structure infections and community acquired bacterial pneumonia, but it is unknown how ceftaroline is being used in real-world settings or how adverse effects (AEs) and mortality compare to clinical trials. Objective This study describes ceftaroline use, AEs, and mortality in U.S. Veterans Health Administration (VHA) hospital patients. Methods This phase 4, population-based, epidemiologic study analyzed patients ≥18 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…Eleven published studies [6], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18] were found in the literature reporting the successful use of ceftaroline in MRSA bacteremia. 2 matched case-control, 5…”
Section: Bacteremiamentioning
confidence: 99%
“…Eleven published studies [6], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18] were found in the literature reporting the successful use of ceftaroline in MRSA bacteremia. 2 matched case-control, 5…”
Section: Bacteremiamentioning
confidence: 99%
“…For instance, Staphylococcus aureus remains a leading cause of bacteremia and endocarditis, with an increasing preponderance due to methicillin-resistant S. aureus (MRSA) strains [1, 2]. Given the limitations of the currently available antibiotics (eg, vancomycin) for treating MRSA infections, including drug intolerance, adverse events, and/or clinical failure [3, 4], new antibiotics with anti-MRSA activity have been recently developed.…”
mentioning
confidence: 99%
“…Postmarketing data are important for detecting unexpected adverse events associated with newly marketed drugs, especially when they are utilized for “off-label” use, an increasingly common practice for multidrug-resistant organism (MDRO) infections with limited treatment options. As such, ceftaroline has been utilized to treat MRSA bacteremia, endocarditis, and orthopedic infections [3, 10]. For these indications, ceftaroline has often been utilized for longer treatment durations (up to ≥6 weeks).…”
mentioning
confidence: 99%
“…In a rabbit osteomyelitis model with MRSA it was superior to vancomycin [66] . Data for human osteomyelitis are numerous but anecdotal [67] . In these few reports and a recent review of roughly 180 osteomyelitis cases in the USA [67] , ceftaroline reveals similar success rates to comparator drugs [67][68][69] , but studies are clearly needed [69] .…”
Section: Recent Antibiotics In the Market And Scientific Evaluation Cmentioning
confidence: 99%